(untitled) (Journal of Vishwa Adarsha College, 2025)
This study explored the influence of institutional ownership, resource viability, and digital literacy on the impact of COVID-19 on media education in private and public colleges in Nepal. Utilizing a mixed-methods approach, two colleges were purposively selected to examine the experiences of administrators, lecturers, and students during the transition from in-person to online learning. The research first documented their experiences during this shift in academic delivery, followed by a critical analysis of how varying levels of digital literacy affected the teaching and learning of media-related courses during the pandemic. The key findings of the study showed that private colleges experienced financial setbacks, which hindered their overall performance. In contrast, public colleges got support from the University Grants Commission and local governments. However, they struggled to initiate remote classes for financially disadvantaged and digitally disconnected students. In both kinds of institutions, digital inequalities have had a significant impact on both teaching and administrative effectiveness. Delivering practical skills in media-related courses was another challenge for both. This study still seemed relevant because it provides insights into stakeholders’ digital literacy, ICT integration in education, and disaster and crisis preparedness in the educational sector.